Comparative Analysis Of Financial Performance at PT. Bank SUMUT Before and During the Covid-19 pandemic in Indonesia - Syahyunan; Amlys Syahputra Silalahi; Aryanti Sarartha Sianipar; Sukma, Kirana Rahmalia (Journal Of Management Analytical and Solution (JoMAS), 2022)
This study aims to analyze and compare the financial performance of PT. Bank SUMUT before and during Covid-19 pandemic in Indonesia. This study uses the CAMEL method in the selection of financial ratios to be compared. The financial ratios to be compared are the Capital Adequacy Ratio (CAR), the Non Performing Loan (NPL) ratio, the Return on Assets (ROA) ratio, the Operating Cost and Operating Income (BOPO) ratio, and the Loan to Deposit Ratio (LDR).Â  Data analysis techniques are independent sample t-test on data with normal distribution and Mann-Whitney on data that are not normally distributed. The results showed that the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL) ratio, Return On Assets (ROA), ratio of Operating Costs and Operating Income (BOPO) and, Loan to Deposit Ratio (LDR) ratio there were significant differences between before and during the Indonesian Covid-19 pandemic at PT. Bank SUMUT. Â